2019
DOI: 10.1007/s40430-019-1979-1
|View full text |Cite
|
Sign up to set email alerts
|

A study on the 3D fluid flow of MHD micropump

Abstract: In this paper, a 3D model of magnetohydrodynamic (MHD) micropump with a rectangular channel was modeled and numerically simulated based on the finite volume method. Effects of geometrical parameters such as depth, width, and length of the side electrodes were studied on the maximum flow rate, maximum pressure, and energy rate of the rectangular MHD channels in constant electric current and constant power supply modes. The multiple attributes decision-making method was used in order to identify the most effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…As mentioned in the result sections, the novel arrayed electromagnetic pump structure could create any type of velocity and pressure profile, which is necessary in various applications. In other works, velocity profiles are not controllable and are highly influenced by the fluid and pump parameters [10,18,[21][22][23]. Figure 21a shows the velocity profile in different Hartman numbers (different fluids).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the result sections, the novel arrayed electromagnetic pump structure could create any type of velocity and pressure profile, which is necessary in various applications. In other works, velocity profiles are not controllable and are highly influenced by the fluid and pump parameters [10,18,[21][22][23]. Figure 21a shows the velocity profile in different Hartman numbers (different fluids).…”
Section: Discussionmentioning
confidence: 99%
“…Zakeri et al in 2019, used finite volume method and numerically studied the effect of geometrical parameters, such as depth, width, and length of the side electrodes, on micro pump performances with a rectangular channel. They showed that a wider channel with long electrodes could be used in favor of high performance for high flow rates, high pressure, and energyefficient demands [21]. In 2020, Lee et al numerically investigated the effect of flow velocity, applied voltage, magnetic flux density, Hartman number, and so forth on MHD pump performance in microchannel cooling system for heat dissipating element with different nanofluids [22].…”
Section: Introductionmentioning
confidence: 99%
“…Gedik et al [4] numerically investigated MHD pressure induced flow through a pipe in the absence of slip conditions. A numerical simulation based on the finite volume method was employed by Azimi-Boulali et al [5] to investigate a 3D model of Newtonian magnetohydrodynamic fluid flow. Zaman et al [6] presented the exact solution of unsteady MHD fluid flow in a channel under the influence of heat transfer and slip conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In another investigation, Patel and Kassegne [5] conduct an analytical effort to investigate different flow channel geometries, effects of nonuniform magnetic and electric fields, Joule heating, and electroosmosis in MHD micropumps; here, they use saline solutions based on sodium chloride (NaCl). The reader can review other investigations on MHD micropumps handling homogeneous single-phase fluids such as the studies conducted by Homsy et al [11], Chatterjee and Amiroudine [16], Bau et al [17], Rivero [18], Azimi-Boulali et al [19], Moghaddam [20], Jian and Chang [21], Mondal and Wongwises [22], and many others cited in these works.…”
Section: Introductionmentioning
confidence: 99%